MANUFAKTUR DAN PENGUJIAN KAPASITAS MESIN PENGUPAS KEDELAI JENIS SCREW - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Modernization of tempe fac(oryrequires investment of several processing machines. Soybeanhuller if the most critical among others and plate model is the most commonly utilized. Mr. Mudjijana designed huller screw model, which provide more contact surface between the screw and the housing but more gentle in forcing the hull to get off the beans. Thismodel proved to provide better separation and consequently reduce loss from broken beans. The model prototype was filed for patent in December2004and has beengranteda patent in Feb 1(jh 2010. The currentproject attempting to manufacture the huller and utilize it in the real tempe processing business. Evaluation of huller performance, technically as well as economically, will be evaluated in this project. A wooden soybean huller model has been made which is then used to form mould using a sand template. A liquefied aluminum waspoured in the template to form the screw and its housing. The screw is than connected to the central part at both ends, which is supported by sliding supports. Thescrew rotation is powered by electro motor through V-belt transmission in which the rotation can be adjusted using inverter. The screw was installed into the housing and set as a screw mill and tested for soybean huller. Upon test using boiled soybeans as materials it was found that about 60% of the soybeans were cleaved into two cotyledons. Themill that already manufactured has the milling capacity of 16 kg per hour. Thehuller still need further adjustment to reduce clearance between screw and housing to improve milling performance. The manufacturing of larger mill with 32 kg/hr capacity is still underway. The later size will be able to support a tempe factory with capacity of 250. kg soybeans/day or 500 kg of tempe/day.